COMMUNITY BASED HEALTH PROMOTION INTERVENTIONS FOR NONCOMMUNICABLE DISEASES; A NARRATIVE REVIEW OF GLOBAL EVIDENCE - Khan, Shahzad Ali; Zaman, Tabinda; Pervaiz, Farrah; Zaidi, Sabeen Khurshid; Abbas, Safdar; Majeed, Syed Muhammad Imran (Pakistan Armed Forces Medical Journal, 2015)
Objectives: The objective of this review was to gather evidence of community based health promotion projects at global level. It was also to ascertain lessons learnt and good practices regarding the prevention and control of NCDs globally. Study Design: Descriptive study. Methodology: An online search was conducted for identifying and reviewing community based health promotion models for NCD prevention and control at global level. Titles were scrolled and those articles having community component and NCD related intervention were included in the review. Results: Findings of the review suggest that there are many successful community based models for health promotion at global level dating back to seventies (1970s). Most of the projects were developed Europe and Americas, but there are some good examples of such models in the developing countries as well. Evaluations of many community based health projects show that they are feasible and practical and also result in lowering the morbidity as well as mortality through reduced risk factor prevalence in the community. Conclusion: Community based health promotion projects have been successful in lowering morbidity and mortality in project areas. Community based models for NCD prevention and control are not only costeffective but also can be replicated. So there is need for initiating community based health promotion projects as the burden of disease for NCDs in on the rise in Pakistan.